Applied Physiology in Intensive Care Medicine 2 Physiological Reviews and Editorials - Pinsky, Michael R.; Brochard, Laurent; Mancebo, Jordi; Antonelli, Massimo (Springer Berlin Heidelberg : Imprint: Springer, 2012)
The two previous editions of Applied Physiology in Intensive Care Medicine proved extremely successful, and the book has now been revised and split into two volumes to enhance ease of use. In this second volume some of the most renowned experts in the field offer detailed reviews on measurement techniques and physiological processes of crucial importance in intensive care medicine. Throughout, a key aim is to help overcome the fundamental unevenness in clinicians' understanding of applied physiology, which can lead to suboptimal treatment decisions.   Applied Physiology in Intensive Care has been written by some of the most renowned experts in the field and provides an up-to-date compendium of practical bedside knowledge essential to the effective delivery of acute care medicine. It will serve the clinician as an invaluable reference source on key issues regularly confronted in everyday practice.